2022
DOI: 10.18632/aging.203809
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of chaperonin containing TCP1 subunit 7 has diagnostic and prognostic value for hepatocellular carcinoma

Abstract: Chaperonin containing TCP1 subunit 7 (CCT7) regulates the expression of many tumor-related proteins. We investigated the diagnostic and prognostic value of CCT7 expression for hepatocellular carcinoma (HCC). In datasets from The Cancer Genome Atlas and the Gene Expression Omnibus, CCT7 mRNA levels were greater in HCC tissues than adjacent normal tissues, and these results were validated using immunohistochemistry. In patients with early-stage disease and low alpha-fetoprotein expression, CCT7 expression was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…CCT7 has diagnostic and prognostic value for HCC. [ 57 ] High PRC1 expression in HCC is associated with poor prognosis and low macrophage infiltration. [ 58 ] This finding is consistent with the results of the present analysis.…”
Section: Discussionmentioning
confidence: 99%
“…CCT7 has diagnostic and prognostic value for HCC. [ 57 ] High PRC1 expression in HCC is associated with poor prognosis and low macrophage infiltration. [ 58 ] This finding is consistent with the results of the present analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, KEGG and GSEA analysis revealed that SNRPA was involved in the spliceosome signaling pathway. Interestingly, numerous studies have shown that spliceosome signaling contributed enormously to the tumorigenesis and advancement of multiple tumor types ( 27 , 40 , 41 ). More importantly, in our previous study, the genes most relevant to survival were mainly enriched in the spliceosome pathway in the GEPIA database ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, numerous studies have shown that spliceosome signaling contributed enormously to the tumorigenesis and advancement of multiple tumor types ( 27 , 40 , 41 ). More importantly, in our previous study, the genes most relevant to survival were mainly enriched in the spliceosome pathway in the GEPIA database ( 40 ). Based on the above research results, it is reasonable to speculate that SNRPA functions as an oncogene that promotes HCC tumorigenesis and progression via the spliceosome signaling pathway, which needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The low survival rate of patients with HCC is due to the low detection rate in early HCC and early recurrence post-curative resection. 5 Although diagnostic and prognostic biomarkers have been identi ed in recent years, their poor sensitivity and speci city limit clinical application. 6,7 Therefore, new diagnostic and prognostic molecular biomarkers and the relevant molecular mechanisms and signaling pathways urgently need to be identi ed to improve the prognosis of patients with HCC.…”
Section: Introductionmentioning
confidence: 99%